Pengaruh Struktur Modal dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan LQ45 - Juwita Dewi Syafitri (ARZUSIN, 2025)
This study is motivated by inconsistencies in previous findings regarding the factors influencing financial performance, particularly in companies listed under the LQ45 index. The objective of this research is to analyze the effect of capital structure, measured by the Debt to Asset Ratio (DAR), and firm size on the financial performance of LQ45 companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia or BEI) during the 2014–2023 period. A quantitative approach was used with purposive sampling, resulting in 15 companies selected from the total 45 in the LQ45 index, with a ten-year observation period. Data were obtained from annual financial reports and analyzed using panel data regression with EViews 12 software. The results show that capital structure has a negative and significant effect on financial performance, while firm size has a positive and significant effect. These findings indicate that increased debt burden tends to reduce financial performance, whereas larger firm scale contributes positively to achieving better financial outcomes. This study offers practical implications for investors in making investment decisions and serves as an empirical reference for future research related to financial performance analysis in the Indonesian capital market.